Uptake mechanism of metabolic-targeted gold nanoparticles. (20th July 2018) - Dreifuss, Tamar; Ben-Gal, Tal-Shachar; Shamalov, Katerina; Weiss, Aryeh; Jacob, Avi; Sadan, Tamar; Motiei, Menachem; Popovtzer, Rachela
Aim: To elucidate the interactions, uptake mechanisms and cytotoxicity profile of glucose-functionalized gold nanoparticles (2GF-GNPs), for expanding and advancing the recently proposed technology of metabolic-based cancer detection to a variety of cancer diseases.Methods: Several cell types with different metabolic features were used to assess the involvement of GLUT-1 and different endocytosis pathways in 2GF-GNP uptake, and the cytotoxicity profile of 2GF-GNPs.Results: Cellular uptake of 2GF-GNP strongly correlated with GLUT-1 surface expression, and occurred mainly through clathrin-mediated endocytosis. 2GF-GNPs showed no toxic effect on cell cycle and proliferation.Conclusion: These findings promote development of metabolic-based cancer detection technologies, and suggest that 2GF-GNPs may enable specific cancer detection in a wide range of tumors characterized by high GLUT-1 expression.